Critical singular problems on unbounded domains - D. C. de Morais Filho; O. H. Miyagaki (Abstract and Applied Analysis)
We present some results of existence for the following problem: −Δu=a(x)g(u)+u|u|2∗−2, x∈ℝN(N≥3), u∈D1,2(ℝN), where the function a is a sign-changing function with a singularity at the origin and g has growth up to the Sobolev critical exponent 2∗=2N/(N−2).